Problems Facing Women To Get Benefit From Micro Finance Projects In Khartoum State, Sudan - Mamoun Ahmed, Mohamed Elnur (University of eloued - جامعة الوادي, 2017)
This study examined the problems facing women to get benefit from microfinance projects in Khartoum state- Sudan. A simple random sample was taken from beneficiaries of microfinance services project (117) beneficial to represent the research community. The study is based on the preliminary information that was gathered by the questionnaire (administered by the researcher himself). The other secondary information was collected from scientific research works, books, the internet, and the relevant institutions. Statistical packages for social sciences (SPSS) were used to display and interpret the data; descriptive statistic was used to describe the sample (e.g. percentage and frequency distribution). The study has established some results focused on the Lack of awareness of banking policies, private loans, and repayment, moreover a Lack of experience in project management. Furthermore, the study has proposed a number of recommendations, concentrated on the creation of an environment favorable to the development and growth of microfinance institutions in support of women's funding and Increase the chances of continuous training while reducing costs, and the capacity building of human capital in the field of microfinance, as well as the Intensify training and awareness programs for women in the field of project preparation and banking transactions.
مقال
Keywords: microfinance projects, financial system, Microcredit, women entrepreneurs.